The review of heterogeneous design frameworks/Platforms for digital systems embedded in FPGAs and SoCs - Abdelhakim Alali; Hasna Elmaaradi; Mohammed Khaldoun; Mohamed Sadik (IAES Indonesian Section, 2021)
Systems-on-a-chip integrate specialized modules to provide well-defined functionality. In order to guarantee its efficiency, designersare careful to choose high-level electronic components. In particular,FPGAs (field-programmable gate array) have demonstrated theirability to meet the requirements of emerging technology. However,traditional design methods cannot keep up with the speed andefficiency imposed by the embedded systems industry, so severalframeworks have been developed to simplify the design process of anelectronic system, from its modeling to its physical implementation.This paper illustrates some of them and presents a comparative studybetween them. Indeed, we have selected design methods of SoC(ESP4ML and HLS4ML, OpenESP, LiteX, RubyRTL, PyMTL,SysPy, PyRTL, DSSoC) and NoC networks on OCN chip (PyOCN)and in general on FPGA (PRGA, OpenFPGA, AnyHLS, PYNQ, andPyLog).The objective of this article is to analyze each tool at several levelsand to discuss the benefit of each in the scientific community. Wewill analyze several aspects constituting the architecture and thestructure of the platforms to make a comparative study of thehardware and software design flows of digital systems.